The Implementation of Green Practices on Guest Satisfaction and Revisit Intention at Hotel Komune and Beach Club Bali - Desak Nyoman Dewantari; Ni Made Ernawati; I Ketut Budarma; Gede Ginaya (Bali Membangun Bali: Jurnal Bappeda Litbang, 2026)
Purpose: This research aims to examine the implementation of green practices affects guest satisfaction and revisit intention at Hotel Komune and Beach Club Bali. Research methods: The study employed a quantitative research method using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the relationship between green practices, guest satisfaction, and revisit intention. Additionally, a qualitative method was used to support the quantitative findings through Focus Group Discussion (FGD) with hotel management to gain insights into the practical application and perception of green practices at the hotel. Results and discussion: Green practices have a positive and significant influence on both guest satisfaction and revisit intention. Guest satisfaction also has a significant effect on revisit intention, and it acts as a mediating variable between green practices and revisit intention. The sub variables: green action, green food, and green donation are all well-implemented, but areas like waste bin availability and environmentally friendly food product usage require further improvement. Guest who are satisfied with the hotel’s sustainable practices are more likely to return and recommend the hotel to others. Implication: This study suggests that implementing green practices not only supports environmental sustainability but also serves as an effective business strategy for increasing guest loyalty and satisfaction.